2000
DOI: 10.1046/j.1365-2281.2000.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated standardized pupillometry with optical method for purposes of clinical practice and research

Abstract: The aim of the current study was the introduction and standardization of two experimental conditions for dynamic pupillometry. Pupillometry is a method that can provide valuable data concerning the functioning of the autonomous nervous system. The system for recording the pupil reaction was developed in the Laboratory of Clinical Neurophysiology of the 1st Department of Neurology of Aristotle University of Thessaloniki, in co-operation with the Laboratory of Fluid Mechanics of the Aristotle University of Thess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 33 publications
6
98
0
8
Order By: Relevance
“…We found that the response of the dark-adapted pupil to the first light stimulus was variable and often contaminated by movement artifact. After four conditioning light stimuli, the pupillary light response stabilized (figure 1A), an observation also seen in previous studies with human subjects (Fotiou et al, 2000). The last three pupillary light responses in the sequence were reproducible, and we used the average of these three responses for further analysis.…”
Section: Pupillometrysupporting
confidence: 66%
See 3 more Smart Citations
“…We found that the response of the dark-adapted pupil to the first light stimulus was variable and often contaminated by movement artifact. After four conditioning light stimuli, the pupillary light response stabilized (figure 1A), an observation also seen in previous studies with human subjects (Fotiou et al, 2000). The last three pupillary light responses in the sequence were reproducible, and we used the average of these three responses for further analysis.…”
Section: Pupillometrysupporting
confidence: 66%
“…Likewise the ratio between the initial pupil diameter and the peak constriction is expressed as the relative peak constriction amplitude. Relative peak constriction amplitude is the most commonly used single quantitative measure of the pupillary light reflex (Fotiou et al, 2000).…”
Section: Determination Of Static and Dynamic Pupil Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Owing to the pupils exclusive autonomic innervation, more recently an interest has emerged to measure the pupil diameter to obtain a direct impression of autonomic function. [53][54][55][56] A dilation of the pupil is a result of simultaneous increasing activity of the sympathetic system and decreasing parasympathetic activity. 45,47,49 There is a lack in the literature accounting for some of the neurophysiological effects that seem to take place following manipulation techniques.…”
mentioning
confidence: 99%